Energy : Low Carbon Emissions Scenarios in Brazil - Schaeffer, Roberto; Szklo, Alexandre; de Gouvello, Christophe (World Bank, Washington, DC, 2017)
This report synthesizes the findings for the energy sector of a broader study, the Brazil low carbon study, which was undertaken by the World Bank in its initiative to support Brazil's integrated effort towards reducing national and global emissions of greenhouse gases while promoting long term development. The main aim of the study is to examine the potential for abating Greenhouse Gas (GHG) emissions in Brazil in the energy area and to assess the relative costs of doing so for the time frame 2010-2030. Basically the study seeks to demonstrate by how much, by when and at what cost Brazil could reduce its GHG energy sector emissions. Given its special features, the fuel use and emissions of greenhouse gases in the transportation sector are dealt with in another report of this project. In addition the study aims to provide information for the Brazilian government to enable it to develop a long-term strategy (2030) for reducing carbon in the energy area (except the transport sector) and, more specifically, to provide the technical input needed for evaluating the potential for reducing greenhouse gas emissions produced by the key economic sectors. In short, the study seeks to identify the different options and opportunities that could justify possible international resources being allocated to Brazil. The teams involved in the study needed first to focus on the proposed mitigation and carbon sequestering options and then, after identifying these proposals, to focus on existing barriers to the successful deployment of these options and suggest a set of public policies which could be mobilized to overcome them. The study also provides estimates of the scale of investments and operating costs likely to be involved, as well as a mitigation cost curve.